Penerapan Pendekatan Saintifik dan Normatif dalam Pembelajaran Aqidah Akhlak di Madrasah Ibtidaiyah - Mundir, Mundir (Jurnal Pendidikan Islam Indonesia, 2017)
Learning paradigm shift mandates the learning process that truly empower, explore the creativity of students during fun and innovative learning. 2013 Curriculum (K-13) recommending scientific approach as an approach in any learning is realized in the form of active learning, including Aqidah Akhlak learning. This study focus on how planning of scientific and normative approach in Aqidah Akhlak learning in elementary school, how to apply and how to evaluate learning? With a naturalistic approach and case study, the results showed the following results: 1) Planning of learning that are intra-curricular carried out in the form of lesson plan (RPP) K-13 version and school-based curriculum (KTSP) conditionally, while planning extra-curricular learning to do since the beginning of the first semester. 2) Practice learning to use a scientific approach, the normative approach, and the approach to practice. 3) Learning evaluation conducted on the readiness of students in the learning process, the learning process and learning outcomes, with authentic and holistic approach to assessmen.